Social Norms and Potency of Local Wisdom as A Social Enforcement of Smoking Behavior - Hari Mulyawan, Ketut; Kerta Duana, Made; Kurniati, Ni Made; Rosi Arista Dewi, Kadek; Suarjana, Ketut (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Since 2013, the government of Denpasar City has adopted smoke-free law (KTR). However, the implementation of this law faces several obstacles, one of which is the high social acceptability of smoking in the community. Cigarettes and smoking have been deeply embedded within social and cultural life of the community and become part of the hospitality. Hence, this study aims to explore the social norms of smoking and the potency of local wisdom as a social enforcement for smoking behavior particularly at worship places. This study was a qualitative study located in four sub-districts in Denpasar. Informants and participants were selected purposively. Data was collected through in-depth interviews and FGDs. The study succeeded in interviewing 14 informants and conducting 3 FGDs. The results show that smoking in public places remains common among male, particularly adolescents and the elderly. Smoking behavior is perceived as group identity, however also considered less beneficial due to moral value. Community leaders also noticed smoking in public places. Hence, those leaders have important role to control smoking behavior in public places. Moreover, public education, supervision and enforcement should be considered to engage cultural approach and establish local policy which could accelerate the social enforcement in the community.